Online Learning Media through Open Library System - Nofha Rina; Lucy Pujasari Supratman (Nyimak: Journal of Communication, 2022)
Teaching and learning activities which supported by the Open Library system in Telkom University during COVID-19 pandemic has made the online learning process easier. The readiness of Open Library system has facilitated the learning process which conducted by the users in fulfilling their needs.  The facilities are the online e-catalogue, ask a librarian through social media, virtual discussion room reservation, and literacy online classes.  The Open Library system of Telkom University has turned to be the foremost media in the COVID-19 era.  It also offered the online e-resources services through Whastapp and Instagram related to the information needed by the students and the online books lending to borrow the references. We used descriptive qualitative method. The data collecting was interview and observation. The participated informants to be interviewed were Telkom University students.  The results of this study indicated the Open Library system of Telkom University had encouraged students to maximize the use of Open Library system facilities. Keywords: Online learning, media, open library, students ABSTRAKKegiatan belajar mengajar yang didukung dengan sistem Open Library di Universitas Telkom selama masa pandemi COVID-19 membuat proses pembelajaran online menjadi lebih mudah. Kesiapan sistem Open Library telah memudahkan proses pembelajaran yang dilakukan pengguna dalam memenuhi kebutuhannya. Fasilitas yang diberikan oleh Open Library adalah e-katalog online, bertanya kepada pustakawan melalui media sosial, reservasi ruang diskusi virtual, dan kelas literasi online. Sistem Open Library Universitas Telkom menjadi media terdepan di era COVID-19. Selain itu, Open Library menawarkan layanan online e-resources melalui Whastapp dan Instagram terkait informasi yang dibutuhkan mahasiswa dan peminjaman buku online untuk meminjam referensi. Kami menggunakan metode deskriptif kualitatif. Pengumpulan data dilakukan dengan wawancara dan observasi. Informan yang berpartisipasi untuk diwawancarai adalah mahasiswa Telkom University. Hasil penelitian ini menunjukkan sistem Open Library Universitas Telkom telah mendorong mahasiswa untuk memaksimalkan penggunaan fasilitas sistem Open Library.Kata Kunci: Pembelajaran online, media, perpustakaan terbuka, mahasiwa